2022
DOI: 10.3389/fpsyg.2022.855171
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Refugee Peers – Differences Between Own Preferences and Expectations of the Peer Group

Abstract: Given the high numbers of refugees from Syria entering Germany in the recent years, the social integration of refugee youth has become an increasingly important issue in Germany. Thus, the current study examines adolescents’ decisions and reasoning around the inclusion of Syrian peers in Germany. Using a hypothetical scenario, we assessed adolescents’ (N = 100, M = 13.65 years, SD = 1.93, 51 females, 49 males) peer inclusion decisions and reasoning with attention to comparing inclusion of a Syrian refugee peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Since the beginning of the war in Syria, many researchers have conducted studies on Syrian refugees and refugee adolescents (e.g., [12,20,79,137]). When examining the limited number of studies conducted on refugee adolescents, it can be observed that studies with Syrian adolescents mainly focus on pre-migration risk factors.…”
Section: The Current Studymentioning
confidence: 99%
“…Since the beginning of the war in Syria, many researchers have conducted studies on Syrian refugees and refugee adolescents (e.g., [12,20,79,137]). When examining the limited number of studies conducted on refugee adolescents, it can be observed that studies with Syrian adolescents mainly focus on pre-migration risk factors.…”
Section: The Current Studymentioning
confidence: 99%